New players in the regulation of ecdysone biosynthesis. - Huang, X.; Warren, J.T.; Gilbert, L.I. (Journal of Genetics and Genomics [Yi chuan xue bao], 2008)
Insect ecdysone steroid hormone regulates major developmental transitions, such as molting and metamorphosis. The production of ecdysone correlates well with the timing of these transitions. Finding out how the ecdysone biosynthesis is regulated is crucial to fully understand these sophisticated developmental switches. Here we summarized recent findings in the regulation of ecdysone biosynthesis from the aspects of cell signaling, key biosynthetic enzymes and substrate cholesterol trafficking.